Surgical treatment of aortic valve fibroelastoma : a case report - Šušak, Stamenko S; Okiljević, Bogdan R; Mrvic, Strahinja; Rajić, Jovan; Zdravković, Ranko (Scripta Medica, 2019)
A 45-year-old man was admitted to our Clinic for the first time, with chest pain and fatigue symptoms. CT diagnostics of the chest showed a soft tissue vegetation of approximately 5x5 mm on the left aortic coronary cusp. Also, double-vessel coronary disease was diagnosed. The patient underwent surgery, a complete resection of the tumor was achieved, which was confirmed by postoperative TEE. Because of the risk of valve damage, we decided to replace the aortic valve. Also, a bypass to LAD (LAD-LIMA) and RCA was performed. The patient was discharged on the 14th postoperative day with satisfactory results.